The Influence of Verbal Bullying on Self-Confidence in Fifth-Grade Students at State Elementary School - Jamilah; Khozinul Huda; Fikriyah (Universitas Islam Negeri Palopo, 2025)
This research is motivated by the high number of verbal bullying cases that have a negative impact on students' self-confidence. This study aimed to examine the effect of verbal bullying on the self-confidence of fifth grade students. The method used was descriptive quantitative with a case study approach. From a total population of 86 students, 34 students were selected as a sample with considerations of representativeness and sufficient numbers for simple statistical analysis. Data were collected through a validated and tested questionnaire for reliability, then analyzed using simple linear regression. The results showed that verbal bullying (taunts, insults, and threats) had a significant effect negative relationship with students' self-confidence, with a correlation coefficient of r = 0.369; R² = 0.136; t(32) = -2.243; p < 0.05; and a 95% confidence interval. This means that verbal bullying is associated with 13.6% of the variation in self-confidence, while the rest is influenced by other factors. Although the contribution of influence is relatively small, the practical impact is quite important because victims of verbal bullying tend to hesitate to express their opinions, are afraid to speak in front of the class, and are passive in interacting. These findings align with Erikson's psychosocial theory and Bandura's self-efficacy theory, which explain that negative experiences can lower children's self-confidence. This study is limited by its sample size and limited scope of variables. Therefore, future research is recommended to involve a broader population and consider other psychosocial factors that influence students' self-confidence.